Explaining the depth and breadth of international intelligence cooperation: towards a comprehensive understanding. Issue 1 (2nd January 2021) - Tuinier, Pepijn
ABSTRACT: Despite neorealism's predominance in the academic debate, it is too narrow a basis for the comprehensive understanding of present-day international intelligence cooperation. This approach is perfectly capable of explaining what is currently not happening in international intelligence cooperation and why this is the case. However, it is inadequate to understand what does happen in international intelligence cooperation. To explain international intelligence cooperation, especially in long-standing multilateral arrangements such as the EU and NATO, additional approaches are needed. This article advocates stepping beyond a state-centric approach of international intelligence cooperation, viewing it as a process and using a sociological perspective.